2004
DOI: 10.1016/j.newar.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Detached binaries in the Large Magellanic Cloud

Abstract: Abstract.As a result of a careful selection of eclipsing binaries in the Large Magellanic Cloud using the OGLE-II photometric database, we present a list of 98 systems that are suitable targets for spectroscopic observations that would lead to the accurate determination of the distance to the LMC. For these systems we derive preliminary parameters combining the OGLE-II data with the photometry of MACHO and EROS surveys. In the selected sample, 58 stars have eccentric orbits. Among these stars we found fourteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
2
Order By: Relevance
“…(1) We established high sensibility of the solutions (measured by χ 2 ) to the mass ratio ( Figure 11). This result differed from those of Michalska & Pigulski (2004) and Terrell & Wilson (2005) who found that for detached EBs equally good fits can be obtained in a very large range of mass ratios. We attributed the sensibility of our solutions to the mass ratio to the following: high precision of the Kepler data, very small relative radii of the stars of our sample, and eccentric orbits of our targets.…”
Section: Discussioncontrasting
confidence: 99%
“…(1) We established high sensibility of the solutions (measured by χ 2 ) to the mass ratio ( Figure 11). This result differed from those of Michalska & Pigulski (2004) and Terrell & Wilson (2005) who found that for detached EBs equally good fits can be obtained in a very large range of mass ratios. We attributed the sensibility of our solutions to the mass ratio to the following: high precision of the Kepler data, very small relative radii of the stars of our sample, and eccentric orbits of our targets.…”
Section: Discussioncontrasting
confidence: 99%
“…11). This result differed from those of Michalska & Pigulski (2004) and Terrell & Wilson (2005) who found that for detached eclipsing binaries equally good fits can be obtained in a very large range of mass ratios. We attributed the sensibility of our solutions to the mass ratio to the following reasons: high precision of the Kepler data; very small relative radii of the stars of our sample; eccentric orbits of our targets.…”
Section: Discussioncontrasting
confidence: 99%